STOCK SELECTIVITY ABILITY AND MARKET TIMING PERFORMANCE OF SET 50 INDEX FUND - Saturnwongsa, Toontham; Pongsupatt, Apichat (Journal of Buddhist Education and Research (JBER), 2023)
The objection of this independent study is of stock selectivity ability and market timing performance of set 50 Index fund of 10 set index funds in thailand ,using Treynor and Mazuy (1966) and Henrikeeon and Merton (1981) model. The secondary data on daily net asset value of the mutual fund,one-year Treasury bills and government bound,and the Stock Exchange of Thailand from 1 January 2017 to 31 December 2021. The results in stock selectivity ability and market timing performance of set 50 Index fund .There were 5 funds having stock selectivity ability and 4 Funds having market timing performance,based by The Treynor and Mazuy (1966) model, Henriksson & Merton (1981) model found that there were 4 funds having positive selectivity ability and 2 funds having positive market-timing.